Interplay of rheumatoid arthritis and cardiovascular disease: Insights and prospects - Anastasia V. Poznyak; Nikolay A. Orekhov; Alexey V. Churov; Irina Alexandrovna Starodubtseva; Dmitry Felixovich Beloyartsev; Tatiana Ivanovna Kovyanova; Vasily N. Sukhorukov; Alexander N. Orekhov (SAGE Open Medicine)
Rheumatoid arthritis significantly increases the risk of cardiovascular disease due to chronic inflammation. This review’s purpose is to critically analyze the intricate relationship between rheumatoid arthritis and cardiovascular disease, highlighting the mechanisms by which systemic inflammation contributes to cardiovascular risk and the effectiveness of current treatment strategies. We systematically evaluate existing literature on conventional cardiovascular risk factors in rheumatoid arthritis patients, as well as inflammation-specific markers that influence cardiovascular outcomes. Our conclusions indicate that while several treatment modalities, including methotrexate and other disease-modifying agents, may mitigate cardiovascular risk, there is a prevalent underestimation of true risk by standard cardiovascular disease assessment protocols. This review provides unique contributions by emphasizing the importance of integrating novel risk factors into assessment protocols and advocating for personalized management strategies that cater to the specific needs of rheumatoid arthritis patients. By synthesizing these elements, we aim to enhance understanding and guide clinicians in improving outcomes for rheumatoid arthritis patients at heightened risk of cardiovascular complications.